Pengaruh profitabilitas dan umur perusahaan terhadap ketepatan waktu penyampaian laporan keuangan - Lidya Martha; Gina Gina (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
This study examines the alleged influence of profitability and age of company on the timeliness of submitting financial reports to companies listed on the Indonesia Stock Exchange (BEI). The observation period is from 2015-2019. Purposive sampling is the sampling technique for this research. The number of companies in the research sample was 119 companies with five years of observation, so that the selected sample was 595 observations. The data in this study use secondary data from financial reports listed in the annual report from the BEI homepage, namely www.idx.co.id. The hypothesis in this study using the Binary Response Regression model which consists of Logit Model. The result of this study shows that there is no effect of the profitability variable on the timeliness of companies reporting finances. Different from the profitability variable, the age of the company shows that there is a significant influence on whether or not the company submits its financial statements on time.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack// Keywords: Profitability; age of company; timeliness of financial statements